Kajian Ekonomis Pembangkit Hybrid Renewable Energi Menuju Desa Mandiri Energi di Kabupaten Bone-Bolango - Sabhan Kanata (Universitas Syiah Kuala, 2015)
Energy crisis due to extensive uses of fossil fuel and environmental issues caused by unsustainable uses of energy driving the world and Indonesian government to accelerate the usage of renewable energy such as hydro, wind and solar. One of the government approaches is to implement a program called Independent Energy Village (IEV). Hybrid Optimization Model for Electric Renewables (HOMER) serves to design a micropower systems and to facilitate the comparison between some of power generation technologies. Researcher models the power system based on the physical behavior and overall cost, which are the total cost of installation and operation of the system during operation of the system. HOMER allows researcher to compare various forms of system designs technically and economically. This research was conducted in the village of Lombongo, District Suwawa, in Bone-Bolango Gorontalo. Some of the modeling results showed that the combination of micro-hydro and solar power have the most favorable economic value if operated over 25 years with a Net Present Cost (NPC) is US -369,087.00 and a Level Cost of Energy (LCOE) of -0.106 US/kWh below the level energy costs of PLN at 0.116 US/kWh in whch made this hybrid plant is very competitive. The hybrid plant has micro-hydro generating capacity of 58,9 kW with annual production of 657,384 kW, while solar power plant with a production capacity of 15,7 kW per year 20.091 kW.